Feasibility of gadoteric acid for delayed gadolinium-enhanced MRI of cartilage (dGEMRIC) at the wrist and knee and comparison with Gd-DTPA - Rehnitz, Christoph; Klaan, Bastian; Do, Thuy; Barié, Alexander; Kauczor, Hans-Ulrich; Weber, Marc-André (Journal of magnetic resonance imaging, 2017)
Purpose To assess the feasibility of gadoteric acid for delayed gadolinium-enhanced magnetic resonance imaging of cartilage (dGEMRIC) and to compare the dGEMRIC values obtained using gadoteric acid with those obtained by an equimolar dose of Gd-DTPA. Materials and Methods At 3T, dGEMRIC of the wrist was performed twice using a T1-weighted 3D-volumetric interpolated breath-hold examination sequence in 16 healthy volunteers (10 women; mean age 26.0 years) using gadoteric acid first and Gd-DTPA 3 weeks later. In addition, 24 patients with knee pain were examined using gadoteric acid (n = 12; seven women; mean age 45.8 years) or Gd-DTPA (n = 12; four women; mean age 47.1 years). T1 values, the relative decrease in T1, and the delta R1 were compared using t-tests. Interobserver agreement was assessed using the intraclass correlation (ICC) between two independent readers. Results At the wrist, there was no significant difference in delta R1 values (0.34 ± 0.10/s, 95% confidence interval [0.30;0.38]/s for gadoteric acid and 0.32 ± 0.09 [0.29;0.35]/s for Gd-DTPA, P = 0.24) or the relative decrease in T1 (0.25 ± 0.06 [0.29;0.35] msec for gadoteric acid and 0.24 ± 0.05 [0.22;0.27] msec for Gd-DTPA, P = 0.35). High observer agreement was found at precontrast (ICC = 0.87, P < 0.001) and postcontrast (ICC = 0.89, P < 0.001). Similarly, at the knee, there was no significant difference in delta R1 (0.39 ± 0.18 [0.32;0.47]/s for gadoteric acid and 0.41 ± 0.09 [0.38;0.45]/s for Gd-DTPA, P = 0.59) or the relative decrease in T1 (0.30 ± 0.10 [0.26;0.34] msec for gadoteric acid and 0.33 ± 0.05 [0.30;0.35] msec for Gd-DTPA, P = 0.28). High ICCs of 0.96 (P < 0.01) were noted both at precontrast and postcontrast. Conclusion dGEMRIC using gadoteric acid is feasible and yields comparable values when compared with Gd-DTPA. Level of Evidence: 2 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2017;46:1433-1440.
Gesehen am 27.04.2018